New Aspects of Uptake and Metabolism of Non-organic and Organic Iodine Compounds—The Role of Vanadium and Plant-Derived Thyroid Hormone Analogs in Lettuce - Smoleń, Sylwester; Czernicka, Małgorzata; Kowalska, Iwona; Kȩska, Kinga; Halka, Maria; Grzebelus, Dariusz; Grzanka, Marlena; Skoczylas, Łukasz; Pitala, Joanna; Koronowicz, Aneta; Kováčik, Peter (Frontiers in Plant Science, 2021)
The process of uptake and translocation of non-organic iodine (I) ions, I- and IO3- , has been relatively well described in literature. The situation is different for low-molecular-weight organic aromatic I compounds, as data on their uptake or metabolic pathway is only fragmentary. The aim of this study was to determine the process of uptake, transport, and metabolism of I applied to lettuce plants by fertigation as KIO3, KIO3 + salicylic acid (KIO3+SA), and iodosalicylates, 5-iodosalicylic acid (5-ISA) and 3,5-diiodosalicylic acid (3,5-diISA), depending on whether additional fertilization with vanadium (V) was used. Each I compound was applied at a dose of 10 µM, SA at a dose of 10 µM, and V at a dose of 0.1 µM. Three independent two-year-long experiments were carried out with lettuce; two with pot systems using a peat substrate and mineral soil and one with hydroponic lettuce. The effectiveness of I uptake and translocation from the roots to leaves was as follows: 5-ISA > 3,5-diISA > KIO3. Iodosalicylates, 5-ISA and 3,5-diISA, were naturally synthesized in plants, similarly to other organic iodine metabolites, i.e., iodotyrosine, as well as plant-derived thyroid hormone analogs (PDTHA), triiodothyronine (T3) and thyroxine (T4). T3 and T4 were synthesized in roots with the participation of endogenous and exogenous 5-ISA and 3,5-diISA and then transported to leaves. The level of plant enrichment in I was safe for consumers. Several genes were shown to perform physiological functions, i.e., per64-like, samdmt, msams5, and cipk6.